Disassembly and reassembly of human papillomavirus virus-like particles produces more virion-like antibody reactivity - Zhao, Qinjian (BioMed Central, 2012)
BACKGROUND: Human papillomavirus (HPV) vaccines based on major capsid protein L1 are licensed in over 100 countries to prevent HPV infections. The yeast-derived recombinant quadrivalent HPV L1 vaccine, GARDASIL(R), has played an important role in reducing cancer and genital warts since its introduction in 2006. The L1 proteins self-assemble into virus-like particles (VLPs). RESULTS: VLPs were subjected to post-purification disassembly and reassembly (D/R) treatment during bioprocessing to improve VLP immunoreactivity and stability. The post-D/R HPV16 VLPs and their complex with H16.V5 neutralizing antibody Fab fragments were visualized by cryo electron microscopy, showing VLPs densely decorated with antibody. Along with structural improvements, post-D/R VLPs showed markedly higher antigenicity to conformational and neutralizing monoclonal antibodies (mAbs) H16.V5, H16.E70 and H263.A2, whereas binding to mAbs recognizing linear epitopes (H16.J4, H16.O7, and H16.H5) was greatly reduced. Strikingly, post-D/R VLPs showed no detectable binding to H16.H5, indicating that the H16.H5 epitope is not accessible in fully assembled VLPs. An atomic homology model of the entire HPV16 VLP was generated based on previously determined high-resolution structures of bovine papillomavirus and HPV16 L1 pentameric capsomeres. CONCLUSIONS: D/R treatment of HPV16 L1 VLPs produces more homogeneous VLPs with more virion-like antibody reactivity. These effects can be attributed to a combination of more complete and regular assembly of the VLPs, better folding of L1, reduced non-specific disulfide-mediated aggregation and increased stability of the VLPs. Markedly different antigenicity of HPV16 VLPs was observed upon D/R treatment with a panel of monoclonal antibodies targeting neutralization sensitive epitopes. Multiple epitope-specific assays with a panel of mAbs with different properties and epitopes are required to gain a better understanding of the immunochemical properties of VLPs and to correlate the observed changes at the molecular level. Mapping of known antibody epitopes to the homology model explains the changes in antibody reactivity upon D/R. In particular, the H16.H5 epitope is partially occluded by intercapsomeric interactions involving the L1 C-terminal arm. The homology model allows a more precise mapping of antibody epitopes. This work provides a better understanding of VLPs in current vaccines and could guide the design of improved vaccines or therapeutics.